2006
DOI: 10.13057/biodiv/d070409
|View full text |Cite
|
Sign up to set email alerts
|

The effect of some organic compounds and NAA application on the in vitro growth of the black orchid (Coelogyne pandurata Lindl.)

Abstract: The effect of some organic compounds and NAA application on the in vitro growth of the black orchid (Coelogyne pandurata Lindl.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 0 publications
0
8
0
1
Order By: Relevance
“…The addition of exogenous growth regulators in the form of 150 ml/l coconut water has not been able to increase the number of shoots on MS and VW medium. DI Grow liquid organic fertilizer medium also contains the elements N, P, K, Fe, S, and Zn which are needed in the process of forming new shoots in explants [16]. Meanwhile, Sahtiana et al [17] stated that DI Grow liquid organic fertilizer can replace Vacin and Went medium as an alternative medium for increasing the number of shoots in Vanda tricolor.…”
Section: Increase In Number Of Shootsmentioning
confidence: 99%
“…The addition of exogenous growth regulators in the form of 150 ml/l coconut water has not been able to increase the number of shoots on MS and VW medium. DI Grow liquid organic fertilizer medium also contains the elements N, P, K, Fe, S, and Zn which are needed in the process of forming new shoots in explants [16]. Meanwhile, Sahtiana et al [17] stated that DI Grow liquid organic fertilizer can replace Vacin and Went medium as an alternative medium for increasing the number of shoots in Vanda tricolor.…”
Section: Increase In Number Of Shootsmentioning
confidence: 99%
“…The effect of exogenous concentration is the main factor in propagation activities to obtain optimal plant multiplication levels [10]. The banana extract contains several elements, such as potassium (K), phosphorus (P), and iron (Fe), which positively affect shoot growth [11]. Besides containing auxin, Sprout extract contains the amino acid tryptophan, the most crucial organic substance in auxin biosynthesis, and minerals, such as calcium, iron, magnesium, phosphorus, and zinc, to form shoots [12].…”
Section: Percentage Of Multiplicationmentioning
confidence: 99%
“…This was indicated by the good performance of protocorms, that are green, round with plenty of rhizoids ( Figure 2). Handini et al (2016) reported that VW and KC media can be used for orchid seed germination, whereas the addition of organic materials in VW medium can support the growth of shoots and roots (Untari and Puspitaningtyas 2006). On media VW, protocorms have more numerous and dense rhizoids than on HS and KC media.…”
Section: Germination Test On Different Mediamentioning
confidence: 99%